Growth/differentiation factor 15 (GDF-15) as new potential serum marker in patients with metastatic colorectal cancer - Vocka, Michal; Langer, Daniel; Fryba, Vladimir; Petrtyl, Jaromir; Hanus, Tomas; Kalousova, Marta; Zima, Tomas; Petruzelka, Lubos (Cancer biomarkers, 2018)
BACKGROUND: GDF-15 is a protein belonging to the transforming growth factor beta superfamily that has a role in regulating inflammatory and apoptotic pathways. High level GDF-15 in tumor tissues and plasma correlate with an increased risk of recurrence and reduced overall survival. OBJECTIVE: The aim of this study was to screen GDF-15 capacity to detecting metastatic CRC and compare it with standard tumor markers CEA and CA19-9. METHODS: We collected serum samples from 97 patients with metastatic colorectal cancer and 79 samples from healthy controls. Serum levels of GDF-15, CEA and CA19-9 were measured by immunochemically. A Kaplan-Meier curve was applied for analysis of survival rates, and a log-rank was used for univariate analysis. RESULTS: Serum levels of GDF-15 were significantly higher in patients with colorectal cancer compared to healthy controls (p< 0.001). In addition, serum levels of GDF-15 correlated with extent of liver involvement and patients with higher GDF-15 levels had significantly worse outcome (p< 0.0001). CONCLUSIONS: Our results show GDF-15 as an effective biomarker in patients with metastatic colorectal cancer with the same sensitivity as CEA. In addition, GDF-15 levels strongly correlate with extension of liver involvement in contrast with CEA.
Keywords: senioři; CA-19-9 Antigen; GDF-15; karcinoembryonální antigen; colorectal cancer; kolorektální nádory; Growth Differentiation Factor 15; Prognosis; růstový diferenciační faktor 15; survival; Kaplan-Meier Estimate; Middle Aged; ROC Curve; Colorectal Neoplasms; plocha pod křivkou; mužské pohlaví; Sensitivity and Specificity; Kaplanův-Meierův odhad; míra přežití; Adult; ROC křivka; Biomarkers, Tumor; biomarker; ženské pohlaví; nádorové biomarkery; prognóza; Humans; Carcinoembryonic Antigen; Survival Rate; lidé středního věku; senzitivita a specificita; Area Under Curve; antigen CA-19-9; dospělí; Female; Aged; lidé; Male